Inventarisasi Diversitas Pisces sebagai Alternatif Sumber Belajar Booklet Biologi SMA Kelas X - Poppy Antika Sari; Kasrina Kasrina; Abas Abas; Mareta Widiya; Anggita Dwi Oktaviani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to inventory and classify fish diversity in the Bengkulu traditional market. The research method used is descriptive qualitative. The data obtained were tabulated and analyzed descriptively, then a literature study was conducted for identification. Sample collection was carried out using the exploration method by tracking every trader selling fish in the market. The results showed that there were 55 fish species belonging to 43 genera, 31 families and 9 orders. In conclusion, the order Perciformes with the family Carangidae and the Genus Lutjanus is the most common group of fish found in the Bengkulu traditional market. Keywords: Pocket Book, Sea Fish, Traditional Market, Learning Resources